Teachers' perceptions of school climate in inclusive schools - Pandia, Weny Savitry Sembiring; Purwanti, Margaretha (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2019)
Teachers are important figures in forming the school climate, including in inclusive schools. Their perception will influence the learning process and indirectly affect students’ achievements. This study aimed to identify teachers’ perceptions of school climate in inclusive schools. Mixed method was used in this study. Quantitatively, questionnaires were given to 127 teachers from 2 inclusive vocational schools and 4 inclusive high schools in Jakarta, Bandung, and Surakarta, using accidental sampling technique. In each class, there were 2 – 3 students with special needs, which encompassed different types of disability such as physically disabled, low vision, slow learner, Attention Deficit Hyperactivity Disorder (ADHD) and autism. Qualitatively, school observations and interviews were conducted with 10 teachers. The results showed that their perceptions of the school climate in high schools and vocational schools tended to be positive although the knowledge and application of inclusive education still needed to be improved. There were differences in several perceptual aspects due to the duration of teaching and the type of school.